Evaluation of the potential synergism of imatinib-related poly kinase inhibitors using growth factor stimulated proteoglycan synthesis as a model response. (17th February 2016) - Bernard, Rebekah; Getachew, Robel; Kamato, Danielle; Thach, Lyna; Osman, Narin; Chan, Vincent; Zheng, Wenhua; Little, Peter J
Abstract: Introduction: Tyrosine kinase inhibitors were the first class of smart drugs being specifically designed to inhibit a disease causing target. There is a very important but unresolved question as whether or not the overall therapeutic role of an individual tinib results from an action at its primary target, a single most likely, tyrosine kinase, or from the combined or aggregate action at the multiple targets which each tinib addresses. Methods: We selected a series of ten tinibs (gefitinib, sunitinib, lapatinib, erlotinib, imatinib, sorafenib, axitinib, vanitinib, bosutinib, dasatinib) with various known targets and investigated their activities in the inhibition of proteoglycan synthesis and GAG hyperelongation stimulated by a tyrosine kinase receptor agonist, platelet derived growth factor (PDGF) and for contrast, a serine/threonine kinase receptor agonist, TGF β and some downstream signalling pathways. Results: The inhibitory activity varied from little to total inhibition. The actions of the tinibs were directed more towards inhibition of the tyrosine kinase, PDGF receptor signalling pathway compared to the TGF β. Conclusion: There was no suggestion of any synergistic effect arising from inhibition of multiple kinases as the most potent compound, dasatinib, is known to inhibit the broadest spectrum of kinases.